1997
DOI: 10.2172/551971
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and analysis of end-to-end Internet dynamics

Abstract: Measurements and Analysis of End-to-End Internet Dynamics by Vern Edward Paxson Doctor of Philosophy in Computer ScienceUniversity of California at Berkeley Prof. Domenico Ferrari, ChairAccurately characterizing end-to-end Internet dynamics-the performance that a user actually obtains from the lengthy series of network links that comprise a path through the Internet-is exceptionally difficult, due to the network's immense heterogeneity. It can be impossible to gauge the generality of findings based on measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
303
0
4

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(315 citation statements)
references
References 143 publications
(180 reference statements)
8
303
0
4
Order By: Relevance
“…Further, it has been observed that OWTT variations (for opposite directions) are generally asymmetric, with different delay distributions. They also seem to be correlated with packet loss rates [19]. Periodic delay spikes and packet losses have been observed, which seem to be a consequence of routing flaps [18].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Further, it has been observed that OWTT variations (for opposite directions) are generally asymmetric, with different delay distributions. They also seem to be correlated with packet loss rates [19]. Periodic delay spikes and packet losses have been observed, which seem to be a consequence of routing flaps [18].…”
Section: Introductionmentioning
confidence: 87%
“…Several publications report on the e2e delay performance, and both Round-Trip Time (RTT) and One-Way Transit Time (OWTT) are considered [4,6,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…This includes two standard speech codecs (G.723.1 and G.729) widely used in those types of networks and a simulation of the packet loss patterns inspired in real-traffic measurements [1,14].…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…To compute the bottleneck bandwidth, for outbound traffic, we use Sender Based Packet Pair (SBPP) [16]. SBPP estimates the spacing between a pair of back-to-back TCP packets after passing the bottleneck link between local servers and remote clients by examining the arrival times of their corresponding ACKs.…”
Section: Design Of Rampmentioning
confidence: 99%